Measuring B2B social selling: Key activities, antecedents and performance outcomes - Terho Harri; Giovannetti Marta; Cardinali Silvio (ELSEVIER SCIENCE INC, 2022)
Sales research has widely noted the grow(Davis, Bagozzi, & Warshaw, 1992)ing importance of social media in contemporary B2B selling. Yet, scholars have noted that measurement issues represent a challenge for advancing the study of social media use in selling, since research is lacking on high-rigour measures that provide insights into how salespersons are leveraging social media in their work. Accordingly, this study develops and validates activity-based measures for social selling based on two empirical studies. We find support for all three social selling dimensions of insight generation, connecting and engagement. The findings also extend the current knowledge about the outcomes of social selling by showing that salesperson thought leadership and acquisition performance mediate the sales performance relationship. On the antecedents' side, we show novel evidence that management plays a central role in boosting social selling among the sales force through social media strategy, social media sales tools and firm content support. In turn, sales technology orientation and social influence represent the key individual-level drivers.